ASTRONOMICAL GLASS PLATE NEGATIVES: MONITORING OF EMULSION LAYER DETERIORATION - L. Miskova; P. Novák; R. Hudec; M. Novotná (Acta Polytechnica, 2016)
One of the techniques for making photographic negatives most used in the history of photography were gelatin glass plates. This technique was used not only in the artistic field but also and mainly in the scientific field. The main period when glass plate negatives were used in astronomy was between 1890–1980. There are over 7 million of these negatives all over the word and they carry valuable historical scientific data. However, during the long-term storage of this material, deterioration of the emulsion (picture) layer and/or the support (glass) layer has occurred. In this paper we report on our preliminary results from an analysis of the yellowing of the emulsion layer and of gold micro-spots. Both phenomena worsen the readability of the information in the photograph, and it is necessary to prevent their formation, which is why we need to know as much as possible about their origin.